1986
DOI: 10.1128/mcb.6.9.3117
|View full text |Cite
|
Sign up to set email alerts
|

Rapid enrichment of HeLa transcription factors IIIB and IIIC by using affinity chromatography based on avidin-biotin interactions.

Abstract: Science 222:740-748, 1983). Chromatography of the programmed extract over a biotin-celiulose affinity resin resulted in the selective, and virtually quantitative, retention of one of two stable preinitiation complexes, either VA-IIIC or VA-IIIC-IIIB, depending on the length of template incubation in the S100 extract. After washing the resin with 0.10 M and 0.25 M KCI to remove RNA polymerase HI and nonspecifically bound proteins, respectively, TFIIIC was eluted from the VA-IIIC complex by the addition of 1.5 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The yield of fixation was about 30% as determined by the amount of radioactivity retained on the column and was not improved by increasing the contact times. The reason for this low efficiency is unclear, but it should be pointed out that similar results were obtained by Kasher et al [9] with avidinagarose and biotin-1 1 -dUTP. Moreover, essentially quantitative fixation can be achieved provided that several biotin-1 1-dUTP molecules are attached to the DNA fragment, using terminal deoxynucleotide transferase (Jacques Htrisst, personal communication).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The yield of fixation was about 30% as determined by the amount of radioactivity retained on the column and was not improved by increasing the contact times. The reason for this low efficiency is unclear, but it should be pointed out that similar results were obtained by Kasher et al [9] with avidinagarose and biotin-1 1 -dUTP. Moreover, essentially quantitative fixation can be achieved provided that several biotin-1 1-dUTP molecules are attached to the DNA fragment, using terminal deoxynucleotide transferase (Jacques Htrisst, personal communication).…”
Section: Resultssupporting
confidence: 65%
“…The DNA sequence of interest was ligated to the lactose operator sequence and thus retained on the column. Kasher et al [9] used biotin-cellulose and a biotinylated DNA fragment to obtain a DNA matrix via streptavidin bridges.…”
mentioning
confidence: 99%
“…To this end, we developed an immobilized-ribosomal DNA (rDNA) promoter tem-plate assay similar to those which previously have proven instrumental in the analysis of Pol III and Pol II PICs (2,26,34,39). This assay allowed us to capture and purify Pol I PICs from nuclear extracts and study their fate in the transcription cycle.…”
mentioning
confidence: 99%
“…These include the well-characterized RNA polymerase III and two subcellular fractions which have been functionally designated TFIIIB and TFIIIC. A component in TFIIIC has been shown by physical methods to interact directly with DNA sequences around the B-block consensus element (8,15,22 stoichiometric interaction of TFIIIB with the TFIIIC-VA gene complex, followed by rapid association of RNA polymerase III to form a complete preinitiation complex (8,20).…”
mentioning
confidence: 99%
“…Studies with chromatographically purified transcription complexes have shown that there is a * Corresponding author. stoichiometric interaction of TFIIIB with the TFIIIC-VA gene complex, followed by rapid association of RNA polymerase III to form a complete preinitiation complex (8,20).…”
mentioning
confidence: 99%